2022
DOI: 10.1002/pip.3554
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic material flow analysis of silicon photovoltaic modules to support a circular economy transition

Abstract: Solar photovoltaics (PV) are the fastest growing renewable energy technologies for clean, cheap, and sustainable electricity generation. To prepare for rapid scale-up, the PV industry needs to project material requirements to build out all aspects of the supply chain appropriately and plan to handle large volumes of module waste.Impacts of deploying different material circularity strategies to reduce waste and conserve primary resources need to be quantified to inform sustainable material management. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Several proof-of-concept perovskite recycling line designs were reported to capture nearly 100% of embodied Pb via solvent extraction. Technoeconomic and life cycle analysis of such lines are still missing in the literature. Nonetheless, implementing circular economy principles in this early stage of perovskite PV deployment is essential to phase out module waste and ensure closed-loop materials recycling. …”
Section: Resultsmentioning
confidence: 99%
“…Several proof-of-concept perovskite recycling line designs were reported to capture nearly 100% of embodied Pb via solvent extraction. Technoeconomic and life cycle analysis of such lines are still missing in the literature. Nonetheless, implementing circular economy principles in this early stage of perovskite PV deployment is essential to phase out module waste and ensure closed-loop materials recycling. …”
Section: Resultsmentioning
confidence: 99%
“…The International Renewable Energy Agency (IRENA) reported that global cumulative solar PV waste volumes could reach 78 million metric tons by 2050 [15]. This not only represents a significant challenge in terms of waste management but also represents economic value [16]. The solar PV modules are mainly comprised of lead (Pb), cadmium (Cd), tellurium (Te), copper (Cu), aluminum (Al), and numerous hazardous products that could adversely affect the environment if the panels are damaged and no proper recycling or dumping management is established [15].…”
Section: Introductionmentioning
confidence: 99%
“…At present, photovoltaic modules based on wafer-based crystalline silicon solar cells account for >90% of the global photovoltaic market [1][2][3][4][5]. Laudable enhancements in power conversion efficiency (η) have been experienced for this technology over the last few years, leading to thin film, tandem, and various lab-based architectures [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%